2020
DOI: 10.3390/antiox9050455
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug Resistance Modulation Activity of Silybin Derivatives and Their Anti-Inflammatory Potential

Abstract: Silybin is considered to be the main biologically active component of silymarin. Its oxidized derivative 2,3-dehydrosilybin typically occurs in silymarin in small, but non-negligible amounts (up to 3%). Here, we investigated in detail complex biological activities of silybin and 2,3-dehydrosilybin optical isomers. Antioxidant activities of pure stereomers A and B of silybin and 2,3-dehydrosilybin, as well as their racemic mixtures, were investigated by using oxygen radical absorption capacity (ORAC) and cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 54 publications
(84 reference statements)
2
25
0
Order By: Relevance
“…The Ellman colorimetric method [ 68 ] was used to measure the activity of acetylcholinesterase (AChE). The crude extracts were analyzed using binary dilution in the concentration range of 62.5–0.125 mg/L.…”
Section: Methodsmentioning
confidence: 99%
“…The Ellman colorimetric method [ 68 ] was used to measure the activity of acetylcholinesterase (AChE). The crude extracts were analyzed using binary dilution in the concentration range of 62.5–0.125 mg/L.…”
Section: Methodsmentioning
confidence: 99%
“…P‐glycoprotein does not seem to be very sensitive for inhibition by silymarin or silybin, similarly to other known efflux transporters BCRP and MRP‐1. On the other hand, racemic 2,3‐dehydrosilybin, silychristin A, 2,3‐dehydrosilychristin A, isosilychristin, and anhydrosilychristin had an IC 50 on P‐glycoprotein in the range of 15–26 µM 15,226 . Some organic anion transporting polypeptides (OATP) can be blocked with units of micromolar or even hundreds of nM.…”
Section: Interactionsmentioning
confidence: 99%
“…Since that time, several other studies have analyzed the effect of silymarin or silybin on the expression of cytochrome P450 and P‐glycoprotein 192–195,198,203,230 . Recent studies also showed that anhydrosilychristin and silybin B can substantially decrease the expression of P‐glycoprotein and BCRP, but silybin A, 2,3‐dehydrosilybin (A, B, racemate), and silychristin A had no effect, while 2,3‐dehydrosilychristin only decreased the expression of BCRP 15,226 . A decrease in BCRP expression was also reported previously after treatment with silymarin 220 .…”
Section: Interactionsmentioning
confidence: 99%
“…Silibinin (or silybin) is the major component of silymarin extract from the seeds of Silybum marianum (or milk thistle, Asteraceae) and a member of flavonolignans. (Dobiasová et al, 2020). It receives wide attention due to its anticancer, antioxidant, antibacterial, antifungal, antiinflammatory, cardioprotective, neuroprotective, and hepatoprotective activities (de Oliveira et al, 2015;Shen et al, 2018;Wlcek et al, 2013).…”
Section: Introductionmentioning
confidence: 99%